10th Five Year Plan, 2002 -2007 and Annual Plan 2002-2003 Government of Nagaland - Planning Commission (Planning Commission, 2001)
During 7th plan period 12 post of SDAOs were created. However Subordinate Staff for only 4 SDAOs establishments were created and for the remaining eight SDAO’s establishments created during 7th plan period, no Subordinate posts were sanction. This effects the normal functioning of the establishment. Therefore it is proposed to create the following post during the 10th plan for which the outlay has been projected accordingly.
Department of Agriculture, Government of Nagaland
Department of Agriculture, Government of Nagaland